The Interprofessional Collaborative Organization Map and Preparedness Assessment Tool (IP-COMPASS) - Kathryn Parker; Melissa McGuire; Ivy Oandasan; Rochelle Zorzi (Association of American Medical Colleges, 2012)
Abstract Introduction Organizational culture is a strong force. The underlying culture of a clinical setting can make it easy to deliver interprofessional education (IPE), or it can sabotage it completely. One way of improving the success of your IPE efforts is to better understand the organizational culture, and ways it can be made more conducive to interprofessional learning. In order to address this, we created the Interprofessional Collaborative Organization Map and Preparedness Assessment (IP-COMPASS), a tool for understanding your organizational culture as it relates to IPE. This can be used to help clinical settings prepare to provide intentional interprofessional learning experiences (i.e., learning experiences that help students develop skills for interprofessional collaboration), and enhance interprofessional collaboration amongst healthcare providers within the clinical setting. Methods The IP-COMPASS focuses on 22 specific attributes of clinical settings that influence the ability to deliver IPE. By using IP-COMPASS, a team assessing the attributes, including values and beliefs, structures, practices and behaviors, creates a reflection of the organization's culture. This is helpful in all settings, including those that provide successful IPE learning experiences. By having the IP-COMPASS team explore specific attributes tied to IPE, the team can produce a summary of recommendations as to how to improve IPE in a manner that resonates with educators and organization leaders. Included in this resource are the action planning templates and tools for implementing identified improvements that supports this process. It is recommended that the IP-COMPASS team reconvene 3 to 6 months after the review to discuss progress and identify further actions. Results Pilot testing concluded that the IP-COMPASS is both feasible and useful. The IP-COMPASS was well received and does seem to be valid for the purpose of fostering learning, discussion, and improvement. Discussion The development of the IP-COMPASS harnessed the combined knowledge from existing literature, empirical research, and a wide range of experts. The IP-COMPASS is a unique tool that mobilizes the findings of recent novel research about IPE success factors in a manner that is accessible and useful. It not only fills a knowledge gap, but also supports clinical settings in operationalizing this knowledge.